Wear-resistant porous water permeable brick material and preparation method thereof
By preparing antibacterial curing agents, aqueous epoxy resins and modified nano zinc oxide, and mixing them with epoxy resins and other materials to form gelled materials, the shortcomings of existing permeable brick materials in water retention, wear resistance and antibacterial properties are solved, and efficient water-permeable and wear resistance are achieved.
Patent Information
- Application Number
- CN202411769673.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing permeable brick materials have shortcomings in water retention, wear resistance and antibacterial properties, which limits their application scope.
Using a method of preparing wear-resistant porous permeable brick materials, the antibacterial curing agent, hydrophilic modified aqueous epoxy resin and modified nano zinc oxide supported by surface polyglutamic acid are prepared, and mixed with epoxy resin, cement and other materials to form a gelled material, and finally obtain permeable brick material through casting and molding.
The antibacterial, wear resistance and porous structure of permeable brick materials are achieved, and its permeable water retention properties are significantly improved.
Smart Images

Figure CN119591349A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous materials, and in particular to a wear-resistant porous water-permeable brick material and a preparation method thereof. Background Art
[0002] Permeable bricks, as a widely used high-efficiency pavement permeable material, have alleviated urban waterlogging, heat island effect and the burden on urban drainage systems to a certain extent. Common permeable bricks include concrete permeable bricks, ceramic permeable bricks and sand-based permeable bricks. Among them, sand-based permeable bricks with epoxy resin as binder have the advantages of ordinary permeable bricks, and also have the characteristics of strong anti-clogging performance, good durability and environmental protection; sand-layer top epoxy resin composite permeable bricks refer to quartz sand bonded with epoxy resin and placed on the top layer of permeable bricks. Compared with traditional permeable bricks, this type of permeable brick has the advantages of traditional permeable bricks, and also has the advantages of controllable porosity, good permeability, strong filtration, long service life, good fatigue and chemical corrosion resistance, and simple preparation process.
[0003] Prior art such as Chinese patent CN106747569A discloses a kind of unfired permeable brick which can quickly remove oil stains and its preparation method. By using a binder containing oleophobic and hydrophobic properties, an oleophobic and hydrophobic passage can be formed between a plurality of granular materials, and the oil stains can be quickly drained away through the oleophobic and hydrophobic passage inside the permeable brick, thereby improving the degreasing speed. However, the permeable brick prepared by the permeable brick has poor water retention due to its hydrophobicity, and its wear resistance and antibacterial properties need to be improved, which limits the application of the material. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a wear-resistant porous permeable brick material and a preparation method thereof. The permeable brick material has antibacterial and wear resistance, and has a porous structure and excellent water permeability and water retention performance.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a wear-resistant porous water-permeable brick material comprises the following steps:
[0007] Step (1), preparing an antibacterial curing agent, a water-based epoxy resin and modified nano zinc oxide;
[0008] Wherein, the antibacterial curing agent is prepared by the following steps:
[0009] Polyethylene glycol monomethyl ether methacrylate, 1-vinyl-3-butyl imidazole bromide, acrylamide, water and ammonium persulfate are mixed and reacted, and after the reaction is completed, the mixture is dried to obtain an antibacterial curing agent;
[0010] The waterborne epoxy resin is prepared by the following steps:
[0011] S11, mixing epoxy resin E51, protocatechuic acid and p-toluenesulfonic acid monohydrate, reacting, extracting, separating, taking the organic phase, and drying to obtain a protocatechuic acid-based epoxy resin;
[0012] S12, mixing protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, and ethanol, adding 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt, reacting, and after the reaction is completed, removing most of the solvent by rotary evaporation to obtain a water-based epoxy resin;
[0013] The modified nano zinc oxide is prepared by the following steps:
[0014] S21, adding a regulator to the ethanol aqueous solution to adjust the pH value, adding 3-aminopropyltriethoxysilane dropwise, hydrolyzing after the addition is complete, adding a nano zinc oxide dispersion, reacting, centrifuging, filtering, washing, and drying after the reaction is complete to obtain amino nano zinc oxide;
[0015] S22, mixing L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride with N,N-dimethylformamide, adding amino nano zinc oxide dispersion, reacting, adding ether after the reaction, filtering, washing, and drying to obtain an intermediate product;
[0016] The intermediate product is mixed with a hydrogen bromide acetic acid solution, reacted, and after the reaction is completed, centrifuged, washed, and dried to obtain modified nano zinc oxide;
[0017] Step (2), mixing epoxy resin E51, water-based epoxy resin, active diluent, curing agent, modified nano zinc oxide, and water, adding cement, and continuing to mix until uniformly mixed to obtain a cementitious material;
[0018] The cementitious material is mixed with the base aggregate, and after the mixture is evenly mixed, a base slurry is obtained; the cementitious material is mixed with the surface aggregate, and after the mixture is evenly mixed, a surface slurry is obtained;
[0019] The base layer slurry is poured into a mold, rammed into shape, and the base layer is obtained; the surface layer slurry is poured into the mold filled with the base layer, smoothed so that the surface layer slurry covers the surface of the base layer, vibrated to form, left to solidify, demolded, and cured to obtain a wear-resistant porous permeable brick material.
[0020] Preferably, when preparing the antibacterial curing agent in step (1), the mass ratio of polyethylene glycol monomethyl ether methacrylate, 1-vinyl-3-butylimidazolium bromide, acrylamide, water and ammonium persulfate is 25-30:25-30:50-60:100-120:0.4-0.6; and the reaction conditions are: reacting at a temperature of 50-60°C for 10-12h.
[0021] Preferably, when preparing the waterborne epoxy resin in step (1), in S11: the mass ratio of epoxy resin E51, protocatechuic acid, and p-toluenesulfonic acid monohydrate is 390-420:20-30:3.9-4.2; and the reaction conditions are: reacting in a nitrogen atmosphere at a temperature of 100-120° C. for 5-6 hours.
[0022] Preferably, when preparing the water-based epoxy resin in step (1), in S12: the mass ratio of protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, ethanol, and 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt is 400-420:60-90:30-40:55-65; and the reaction conditions are: reacting at a temperature of 55-65°C for 2-3h.
[0023] Preferably, when preparing modified nano zinc oxide in step (1), in S21: the dripping condition of 3-aminopropyltriethoxysilane is dripping for 8-10 min at a pH value of 4.5-5; the hydrolysis condition is: hydrolysis for 5-7 min at a rotation speed of 300-400 r / min and room temperature; the reaction condition is: react at room temperature for 2-4 h.
[0024] Preferably, when preparing modified nano zinc oxide in step (1), in S21: the mass ratio of ethanol aqueous solution, nano zinc oxide dispersion and 3-aminopropyltriethoxysilane is 140-150:9-11:4.5-5, the ethanol aqueous solution is 95wol% ethanol aqueous solution, and the nano zinc oxide dispersion is prepared by mixing nano zinc oxide and ethanol in a mass ratio of 1:8-10 and ultrasonically dispersing for 10-20 minutes.
[0025] Preferably, the regulator includes a 1 mol / L acetic acid aqueous solution.
[0026] Preferably, when preparing the modified nano zinc oxide in step (1), in S22: the mass ratio of L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride, N,N-dimethylformamide, and amino nano zinc oxide dispersion is 5:90-100:90-100; the amino nano zinc oxide dispersion is prepared by mixing amino nano zinc oxide and N,N-dimethylformamide in a mass ratio of 1:90-100, and ultrasonically dispersing for 10-20 minutes; when preparing the intermediate product, the reaction conditions are: stirring the reaction at a temperature of 0-5°C for 88-96 hours.
[0027] Preferably, when preparing the modified nano zinc oxide in step (1), in S22: the mass ratio of the intermediate product to the 33wt% hydrogen bromide acetic acid solution is 1:25-30, and the hydrogen bromide acetic acid solution is a 33wt% hydrogen bromide acetic acid solution; when preparing the modified nano zinc oxide, the reaction conditions are: reacting under reflux conditions for 2-3h.
[0028] Preferably, in step (2): the mass ratio of epoxy resin E51, water-based epoxy resin, active diluent, curing agent, modified nano zinc oxide, water and cement is 60-80:20-40:10-15:20:10-15:2.2-3:12-18; the curing agent is prepared by mixing the antibacterial curing agent and the curing agent in a mass ratio of 8-10:10-12.
[0029] Furthermore, the active diluent is polyethylene glycol diglycidyl ether; and the curing agent is tetraethylenepentamine.
[0030] Preferably, in step (2), when preparing the gelling material, the mixing conditions are: mixing at a rotation speed of 275-295 r / min and room temperature for 1.5-2 min; and the continued mixing conditions are: mixing at a rotation speed of 135-145 r / min and room temperature for 2-3 min.
[0031] Preferably, in step (2): the mass ratio of cementitious material to base aggregate is 8-10:100; the mass ratio of cementitious material to surface aggregate is 8-10:100; when preparing the base slurry, the mixing conditions are: mixing at a rotation speed of 135-145r / min and room temperature for 1-2min; when preparing the surface layer slurry, the mixing conditions are: mixing at a rotation speed of 135-145r / min and room temperature for 1-2min; the thickness of the surface layer is 0.5-1cm.
[0032] Preferably, in step (2), the base aggregate is basalt; the surface aggregate is prepared by mixing machine-made sand and pretreated polypropylene fiber in a mass ratio of 100:0.5-0.6; the pretreated polypropylene fiber is prepared by soaking polypropylene fiber in a 1-1.5wt% γ-(2,3-epoxypropoxy)propyltrimethoxysilane / ethanol solution for 20-30 minutes and then drying it at 80-100°C for 2-3 hours.
[0033] Preferably, a wear-resistant porous permeable brick material is prepared by the method for preparing the wear-resistant porous permeable brick material as described above.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The present invention prepares an antibacterial curing agent with antibacterial performance, a hydrophilically modified water-based epoxy resin, and a modified nano zinc oxide with polyglutamic acid loaded on the surface, and then mixes the three materials with epoxy resin E51, an active diluent, a curing agent, water, and cement to obtain a cementitious material; basalt is selected as a base aggregate, and machine-made sand and polypropylene fibers treated with a silane coupling agent are used as a surface aggregate, which are respectively mixed with the cementitious materials and then cast to form a surface layer / base composite material, and after solidification and curing, a wear-resistant porous permeable brick material is obtained; the permeable brick material has antibacterial and wear resistance, and due to its porous structure, it has excellent water permeability and water retention performance.
[0036] The present invention polymerizes polyethylene glycol monomethyl ether methacrylate, 1-vinyl-3-butyl imidazole bromide and acrylamide under the action of an initiator through a free radical polymerization reaction to form a polymer with an amino functional group, wherein the polyethylene glycol monomethyl ether methacrylate has hydrophilicity and the 1-vinyl-3-butyl imidazole bromide has good antibacterial performance. The prepared antibacterial curing agent can utilize the amino functional group to participate in the curing reaction of the epoxy resin, and has antibacterial performance and good hydrophilicity, and can further improve the water permeability and water retention performance of the permeable brick;
[0037] The present invention uses p-toluenesulfonic acid as a catalyst, and composites epoxy resin and protocatechuic acid through an esterification reaction to obtain a protocatechuic acid-based epoxy resin with a catechol group on the side chain, and then uses the ring-opening reaction of the epoxy group and the amino group with 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt to introduce a hydrophilic sulfonate group into the main chain of the epoxy resin to make it water-based. The prepared water-based epoxy resin has good hydrophilicity and, because the catechol group has excellent adhesion, the bonding effect of the water-based epoxy resin as a cementitious material component on the aggregate can be enhanced, thereby improving the mechanical properties of the permeable brick material.
[0038] The invention uses an aminosilane coupling agent to perform surface modification on nano zinc oxide, so that its surface is loaded with amino functional groups, and uses the aminosilane coupling agent as an initiator to cause L-glutamic acid-5-benzyl ester-N-carboxyl ring anhydride to form polyglutamic acid benzyl ester by ring-opening polymerization on the surface of the amino nano zinc oxide, and then reacts with a hydrogen bromide acetic acid solution to remove the protective group benzyl, so as to obtain modified nano zinc oxide loaded with polyglutamic acid; wherein, due to the presence of free carboxyl groups in the polyglutamic acid, the polyglutamic acid has excellent water absorption and water retention properties; the nano zinc oxide can improve the antibacterial properties of the substrate as an inorganic antibacterial agent; the modified nano zinc oxide loaded with polyglutamic acid is used as a cementitious material component, so as to improve the water retention properties of the cementitious material, enhance the water permeability and water retention capacity of the permeable brick material, and also improve the antibacterial properties of the permeable brick material;
[0039] The present invention prepares a cementitious material by mixing epoxy resin E51, water-based epoxy resin, active diluent, antibacterial curing agent, curing agent, modified nano zinc oxide, water and cement, respectively mixing with base aggregate and surface aggregate and then pouring to form a surface layer / base composite material, and obtaining a permeable brick material after solidification and curing; wherein the antibacterial curing agent and the modified nano zinc oxide in the cementitious material can synergistically improve the antibacterial performance of the permeable brick material, and the water-based epoxy resin and the modified nano zinc oxide can both improve the water permeability and water retention capacity of the permeable brick material; polypropylene fiber modified by an epoxy silane coupling agent is added to the surface aggregate, and the wear resistance of the permeable brick material is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a process flow chart for preparing wear-resistant porous water-permeable brick materials in the present invention;
[0041] Figure 2 It is a bar graph of water retention rate of the permeable brick materials prepared in the embodiments and comparative examples of the present invention in performance tests;
[0042] Figure 3 It is an antibacterial bar graph of the permeable brick materials prepared in the embodiments and comparative examples of the present invention in the performance test;
[0043] Figure 4 It is a bar graph of the mass loss rate of the permeable brick materials prepared in the embodiments and comparative examples of the present invention in the performance test. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0045] Example 1
[0046] This embodiment discloses a method for preparing a wear-resistant porous water-permeable brick material, comprising the following steps:
[0047] Step (1), preparing an antibacterial curing agent, a water-based epoxy resin and modified nano zinc oxide;
[0048] Wherein, the antibacterial curing agent is prepared by the following steps:
[0049] Polyethylene glycol monomethyl ether methacrylate, 1-vinyl-3-butyl imidazole bromide, acrylamide, water, and ammonium persulfate are mixed in a mass ratio of 25:25:50:100:0.4, reacted at 50° C. for 12 hours, and dried at 50° C. for 56 hours after the reaction to obtain an antibacterial curing agent;
[0050] The waterborne epoxy resin is prepared by the following steps:
[0051] S11, epoxy resin E51, protocatechuic acid, and p-toluenesulfonic acid monohydrate were mixed in a mass ratio of 390:20:3.9, and reacted in a nitrogen atmosphere at 100°C for 6 hours. After the reaction was completed, a crude reaction product was obtained, and water 4 times the mass of the crude reaction product was added for extraction, and the liquids were separated. The organic phase was taken and dried at 50°C for 12 hours to obtain a protocatechuic acid-based epoxy resin;
[0052] S12, mixing protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, and ethanol, adding 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt, reacting at 55° C. for 3 h, and after the reaction, removing most of the solvent by rotary evaporation at 50° C. to obtain a water-based epoxy resin;
[0053] Wherein, the mass ratio of protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, ethanol, and 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt is 400:60:30:55;
[0054] The modified nano zinc oxide is prepared by the following steps:
[0055] S21, add 1 mol / L acetic acid aqueous solution to 95wol% ethanol aqueous solution to adjust the pH value to 4.5, add 3-aminopropyltriethoxysilane dropwise for 8 min, after the addition is completed, hydrolyze at a speed of 300 r / min and room temperature for 5 min, add nano zinc oxide dispersion after hydrolysis, react at room temperature for 2 h, after the reaction is completed, centrifuge, filter, take the filter cake, add 5 times the mass of ethanol to wash three times, dry at 70°C for 16 h, and obtain amino nano zinc oxide;
[0056] The mass ratio of 95wol% ethanol aqueous solution, nano zinc oxide dispersion and 3-aminopropyltriethoxysilane is 140:9:4.5; the nano zinc oxide dispersion is prepared by mixing nano zinc oxide and ethanol in a mass ratio of 1:8 and then ultrasonically dispersing for 10 minutes;
[0057] S22, L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride was mixed with N,N-dimethylformamide, and an amino nano zinc oxide dispersion was added, and the mixture was stirred at 0°C for 96 hours. After the reaction was completed, a crude reaction product was obtained, and ether with a mass of 8 times that of the crude reaction product was added, and the mixture was filtered. The filter cake was taken, and N,N-dimethylformamide and ether with a mass of 8 times that of the filter cake were added in turn for washing, and the mixture was dried at 50°C for 30 hours to obtain an intermediate product;
[0058] The mass ratio of L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride, N,N-dimethylformamide, and amino nano zinc oxide dispersion is 5:90:90; the amino nano zinc oxide dispersion is prepared by mixing amino nano zinc oxide and N,N-dimethylformamide at a mass ratio of 1:90 and then ultrasonically dispersing for 10 minutes;
[0059] The intermediate product was mixed with 33wt% of hydrogen bromide acetic acid solution at a mass ratio of 1:25, and reacted under reflux conditions for 2h. After the reaction was completed, the mixture was centrifuged, and the centrifugal precipitate was taken, and methanol 6 times the mass of the centrifugal precipitate was added to wash three times, and dried at 50°C for 24h to obtain modified nano zinc oxide;
[0060] Step (2), epoxy resin E51, water-based epoxy resin, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, modified nano zinc oxide, and water are mixed at a speed of 275 r / min and room temperature for 2 minutes, cement is added, and mixing is continued at a speed of 135 r / min and room temperature for 3 minutes. After mixing evenly, a cementitious material is obtained;
[0061] Among them, the mass ratio of epoxy resin E51, water-based epoxy resin, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, modified nano zinc oxide, water, and cement is 80:20:10:8:12:10:2.2:12;
[0062] The cementitious material and the base aggregate are mixed at a mass ratio of 8:100 at a rotation speed of 135 r / min and room temperature for 2 minutes, and after mixing evenly, a base slurry is obtained; the cementitious material and the surface layer aggregate are mixed at a mass ratio of 8:100 at a rotation speed of 135 r / min and room temperature for 2 minutes, and after mixing evenly, a surface layer slurry is obtained;
[0063] The base aggregate is basalt; the surface aggregate is prepared by mixing machine-made sand and pretreated polypropylene fiber in a mass ratio of 100:0.5; the pretreated polypropylene fiber is prepared by soaking the polypropylene fiber in a 1wt% γ-(2,3-epoxypropoxy)propyltrimethoxysilane / ethanol solution for 30 minutes and then drying it at 80°C for 3 hours;
[0064] The base layer slurry is poured into a mold and rammed into shape to obtain a base layer; the surface layer slurry is poured into the mold filled with the base layer, smoothed so that the surface layer slurry covers the surface of the base layer, and vibrated to form a surface layer with a thickness of 0.5 cm. It is allowed to stand and solidify for 20 hours, demolded, and cured at a humidity of 90% and a temperature of 18°C for 30 days to obtain a wear-resistant porous permeable brick material.
[0065] Example 2
[0066] This embodiment discloses a method for preparing a wear-resistant porous water-permeable brick material, comprising the following steps:
[0067] Step (1), preparing an antibacterial curing agent, a water-based epoxy resin and modified nano zinc oxide;
[0068] Wherein, the antibacterial curing agent is prepared by the following steps:
[0069] Polyethylene glycol monomethyl ether methacrylate, 1-vinyl-3-butyl imidazole bromide, acrylamide, water, and ammonium persulfate were mixed in a mass ratio of 26:26:53:105:0.5, reacted at 50° C. for 11 hours, and dried at 55° C. for 52 hours after the reaction to obtain an antibacterial curing agent;
[0070] The waterborne epoxy resin is prepared by the following steps:
[0071] S11, epoxy resin E51, protocatechuic acid, and p-toluenesulfonic acid monohydrate were mixed in a mass ratio of 400:23:4, and reacted in a nitrogen atmosphere at 100°C for 5.5 hours. After the reaction was completed, a crude reaction product was obtained, and water 4 times the mass of the crude reaction product was added for extraction, and the liquids were separated. The organic phase was taken and dried at 55°C for 10 hours to obtain a protocatechuic acid-based epoxy resin;
[0072] S12, mixing protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, and ethanol, adding 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt, reacting at 55° C. for 2.5 h, and after the reaction, removing most of the solvent by rotary evaporation at 55° C. to obtain a water-based epoxy resin;
[0073] Among them, the mass ratio of protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, ethanol, and 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt is 405:70:33:58;
[0074] The modified nano zinc oxide is prepared by the following steps:
[0075] S21, adding 1 mol / L acetic acid aqueous solution to 95wol% ethanol aqueous solution to adjust the pH value to 4.8, adding 3-aminopropyltriethoxysilane dropwise for 8 min, and after the addition is completed, hydrolyzing at a speed of 350r / min and room temperature for 6 min, adding nano zinc oxide dispersion after hydrolysis, and reacting at room temperature for 3h. After the reaction is completed, centrifuging, filtering, taking the filter cake, adding ethanol 6 times the mass of the filter cake to wash three times, and drying at 75°C for 14h to obtain amino nano zinc oxide;
[0076] The mass ratio of 95wol% ethanol aqueous solution, nano zinc oxide dispersion and 3-aminopropyltriethoxysilane is 143:9.5:4.6; the nano zinc oxide dispersion is prepared by mixing nano zinc oxide and ethanol in a mass ratio of 1:8 and then ultrasonically dispersing for 15 minutes;
[0077] S22, L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride was mixed with N,N-dimethylformamide, and an amino nano zinc oxide dispersion was added, and the mixture was stirred at 0°C for 92 hours. After the reaction was completed, a crude reaction product was obtained, and ether with a mass of 8 times that of the crude reaction product was added, and the mixture was filtered. The filter cake was taken, and N,N-dimethylformamide and ether with a mass of 8 times that of the filter cake were added in sequence for washing, and the mixture was dried at 55°C for 26 hours to obtain an intermediate product;
[0078] The mass ratio of L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride, N,N-dimethylformamide, and amino nano zinc oxide dispersion is 5:93:93; the amino nano zinc oxide dispersion is prepared by mixing amino nano zinc oxide and N,N-dimethylformamide in a mass ratio of 1:93 and then ultrasonically dispersing for 15 minutes;
[0079] The intermediate product was mixed with 33wt% of hydrogen bromide acetic acid solution at a mass ratio of 1:26, and reacted under reflux conditions for 2.5h. After the reaction was completed, the mixture was centrifuged, and the centrifugal precipitate was taken, and methanol 6 times the mass of the centrifugal precipitate was added to wash three times, and dried at 55°C for 20h to obtain modified nano zinc oxide;
[0080] Step (2), epoxy resin E51, water-based epoxy resin, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, modified nano zinc oxide, and water are mixed at a speed of 280 r / min and room temperature for 2 minutes, cement is added, and mixing is continued at a speed of 140 r / min and room temperature for 3 minutes. After mixing evenly, a cementitious material is obtained;
[0081] Among them, the mass ratio of epoxy resin E51, water-based epoxy resin, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, modified nano zinc oxide, water, and cement is 75:25:12:8.5:11.5:12:2.4:14;
[0082] The cementitious material and the base aggregate are mixed at a mass ratio of 8.5:100 at a rotation speed of 140 r / min and room temperature for 2 minutes, and after mixing evenly, a base slurry is obtained; the cementitious material and the surface layer aggregate are mixed at a mass ratio of 8.5:100 at a rotation speed of 140 r / min and room temperature for 2 minutes, and after mixing evenly, a surface layer slurry is obtained;
[0083] The base aggregate is basalt; the surface aggregate is prepared by mixing machine-made sand and pretreated polypropylene fiber in a mass ratio of 100:0.53; the pretreated polypropylene fiber is prepared by soaking the polypropylene fiber in a 1.2wt% γ-(2,3-epoxypropoxy)propyltrimethoxysilane / ethanol solution for 25 minutes and then drying it at 90°C for 3 hours;
[0084] The base layer slurry is poured into a mold and rammed into shape to obtain a base layer; the surface layer slurry is poured into the mold filled with the base layer, smoothed so that the surface layer slurry covers the surface of the base layer, and vibrated to form a surface layer with a thickness of 0.6 cm. It is allowed to stand and solidify for 24 hours, demolded, and cured at a humidity of 93% and a temperature of 20°C for 28 days to obtain a wear-resistant porous permeable brick material.
[0085] Example 3
[0086] This embodiment discloses a method for preparing a wear-resistant porous water-permeable brick material, comprising the following steps:
[0087] Step (1), preparing an antibacterial curing agent, a water-based epoxy resin and modified nano zinc oxide;
[0088] Wherein, the antibacterial curing agent is prepared by the following steps:
[0089] Polyethylene glycol monomethyl ether methacrylate, 1-vinyl-3-butyl imidazole bromide, acrylamide, water, and ammonium persulfate are mixed in a mass ratio of 28:28:55:110:0.5, reacted at 55° C. for 11 hours, and dried at 55° C. for 52 hours after the reaction to obtain an antibacterial curing agent;
[0090] The waterborne epoxy resin is prepared by the following steps:
[0091] S11, epoxy resin E51, protocatechuic acid, and p-toluenesulfonic acid monohydrate were mixed in a mass ratio of 405:25:4.05, and reacted at 110°C for 5.5 hours in a nitrogen atmosphere. After the reaction was completed, a crude reaction product was obtained, and water 4 times the mass of the crude reaction product was added for extraction, and the liquids were separated. The organic phase was taken and dried at 55°C for 10 hours to obtain a protocatechuic acid-based epoxy resin;
[0092] S12, mixing protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, and ethanol, adding 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt, reacting at 60° C. for 2.5 h, and after the reaction, removing most of the solvent by rotary evaporation at 55° C. to obtain a water-based epoxy resin;
[0093] Among them, the mass ratio of protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, ethanol, and 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt is 410:75:35:60;
[0094] The modified nano zinc oxide is prepared by the following steps:
[0095] S21, adding 1 mol / L acetic acid aqueous solution to 95wol% ethanol aqueous solution to adjust the pH value to 4.8, adding 3-aminopropyltriethoxysilane dropwise for 9 min, and after the addition is completed, hydrolyzing at a speed of 350r / min and room temperature for 6 min, adding nano zinc oxide dispersion after hydrolysis, and reacting at room temperature for 3h. After the reaction is completed, centrifuging, filtering, taking the filter cake, adding ethanol 6 times the mass of the filter cake to wash three times, and drying at 75°C for 14h to obtain amino nano zinc oxide;
[0096] The mass ratio of 95wol% ethanol aqueous solution, nano zinc oxide dispersion and 3-aminopropyltriethoxysilane is 145:10:4.8; the nano zinc oxide dispersion is prepared by mixing nano zinc oxide and ethanol in a mass ratio of 1:9 and then ultrasonically dispersing for 15 minutes;
[0097] S22, L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride was mixed with N,N-dimethylformamide, and an amino nano zinc oxide dispersion was added, and the mixture was stirred at 2°C for 92 hours. After the reaction was completed, a crude reaction product was obtained, and ether with a mass of 10 times that of the crude reaction product was added, and the mixture was filtered. The filter cake was taken, and N,N-dimethylformamide and ether with a mass of 10 times that of the filter cake were added in turn for washing, and the mixture was dried at 55°C for 26 hours to obtain an intermediate product;
[0098] The mass ratio of L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride, N,N-dimethylformamide, and amino nano zinc oxide dispersion is 5:95:95; the amino nano zinc oxide dispersion is prepared by mixing amino nano zinc oxide and N,N-dimethylformamide at a mass ratio of 1:95 and then ultrasonically dispersing for 15 minutes;
[0099] The intermediate product was mixed with 33wt% of hydrogen bromide acetic acid solution at a mass ratio of 1:28, and reacted under reflux conditions for 2.5h. After the reaction was completed, the mixture was centrifuged, and the centrifugal precipitate was taken, and methanol 6 times the mass of the centrifugal precipitate was added to wash three times, and dried at 55°C for 20h to obtain modified nano zinc oxide;
[0100] Step (2), epoxy resin E51, water-based epoxy resin, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, modified nano zinc oxide, and water are mixed at a speed of 285 r / min and room temperature for 1.8 min, cement is added, and mixing is continued at a speed of 140 r / min and room temperature for 2.5 min. After mixing evenly, a cementitious material is obtained;
[0101] Among them, the mass ratio of epoxy resin E51, water-based epoxy resin, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, modified nano zinc oxide, water, and cement is 70:30:13:9:11:13:2.6:15;
[0102] The cementitious material and the base aggregate are mixed at a mass ratio of 9:100 at a rotation speed of 140 r / min and room temperature for 1.5 min, and after mixing evenly, a base slurry is obtained; the cementitious material and the surface layer aggregate are mixed at a mass ratio of 9:100 at a rotation speed of 140 r / min and room temperature for 1.5 min, and after mixing evenly, a surface layer slurry is obtained;
[0103] The base aggregate is basalt; the surface aggregate is prepared by mixing machine-made sand and pretreated polypropylene fiber in a mass ratio of 100:0.55; the pretreated polypropylene fiber is prepared by soaking the polypropylene fiber in a 1.3wt% γ-(2,3-epoxypropoxy)propyltrimethoxysilane / ethanol solution for 25 minutes and then drying it at 90°C for 2.5 hours;
[0104] The base layer slurry is poured into a mold and rammed into shape to obtain a base layer; the surface layer slurry is poured into the mold filled with the base layer, smoothed so that the surface layer slurry covers the surface of the base layer, and vibrated to form a surface layer with a thickness of 0.8 cm. It is allowed to stand and solidify for 24 hours, demolded, and cured at a humidity of 93% and a temperature of 20°C for 29 days to obtain a wear-resistant porous permeable brick material.
[0105] Example 4
[0106] This embodiment discloses a method for preparing a wear-resistant porous water-permeable brick material, comprising the following steps:
[0107] Step (1), preparing an antibacterial curing agent, a water-based epoxy resin and modified nano zinc oxide;
[0108] Wherein, the antibacterial curing agent is prepared by the following steps:
[0109] Polyethylene glycol monomethyl ether methacrylate, 1-vinyl-3-butyl imidazole bromide, acrylamide, water, and ammonium persulfate were mixed in a mass ratio of 29:29:58:115:0.5, reacted at 60° C. for 11 hours, and dried at 55° C. for 52 hours after the reaction to obtain an antibacterial curing agent;
[0110] The waterborne epoxy resin is prepared by the following steps:
[0111] S11, epoxy resin E51, protocatechuic acid, and p-toluenesulfonic acid monohydrate were mixed in a mass ratio of 410:28:4.1, and reacted at 120°C for 5.5 hours in a nitrogen atmosphere. After the reaction was completed, a crude reaction product was obtained, and water 4 times the mass of the crude reaction product was added for extraction, and the liquids were separated. The organic phase was taken and dried at 55°C for 10 hours to obtain a protocatechuic acid-based epoxy resin;
[0112] S12, mixing protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, and ethanol, adding 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt, reacting at 60° C. for 2.5 h, and after the reaction, removing most of the solvent by rotary evaporation at 55° C. to obtain a water-based epoxy resin;
[0113] Among them, the mass ratio of protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, ethanol, and 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt is 415:80:38:63;
[0114] The modified nano zinc oxide is prepared by the following steps:
[0115] S21, add 1 mol / L acetic acid aqueous solution to 95wol% ethanol aqueous solution to adjust the pH value to 5, add 3-aminopropyltriethoxysilane dropwise for 9 min, and after the addition is completed, hydrolyze at a speed of 350r / min and room temperature for 6 min. After the hydrolysis, add nano zinc oxide dispersion and react at room temperature for 3 h. After the reaction is completed, centrifuge and filter to take the filter cake, add ethanol 6 times the mass of the filter cake to wash it three times, and dry it at 75°C for 14 h to obtain amino nano zinc oxide;
[0116] The mass ratio of 95wol% ethanol aqueous solution, nano zinc oxide dispersion and 3-aminopropyltriethoxysilane is 148:10.5:4.9; the nano zinc oxide dispersion is prepared by mixing nano zinc oxide and ethanol in a mass ratio of 1:9 and then ultrasonically dispersing for 15 minutes;
[0117] S22, L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride was mixed with N,N-dimethylformamide, and an amino nano zinc oxide dispersion was added, and the mixture was stirred at 2°C for 88 hours. After the reaction was completed, a crude reaction product was obtained, and ether with a mass of 10 times that of the crude reaction product was added, and the mixture was filtered. The filter cake was taken, and N,N-dimethylformamide and ether with a mass of 10 times that of the filter cake were added in turn for washing, and the mixture was dried at 55°C for 26 hours to obtain an intermediate product;
[0118] The mass ratio of L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride, N,N-dimethylformamide, and amino nano zinc oxide dispersion is 5:98:98; the amino nano zinc oxide dispersion is prepared by mixing amino nano zinc oxide and N,N-dimethylformamide in a mass ratio of 1:98 and then ultrasonically dispersing for 15 minutes;
[0119] The intermediate product was mixed with 33wt% of hydrogen bromide acetic acid solution at a mass ratio of 1:29, and reacted under reflux conditions for 2.5h. After the reaction was completed, the mixture was centrifuged, and the centrifugal precipitate was taken, and methanol 6 times the mass of the centrifugal precipitate was added to wash three times, and dried at 55°C for 20h to obtain modified nano zinc oxide;
[0120] Step (2), epoxy resin E51, water-based epoxy resin, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, modified nano zinc oxide, and water are mixed at a speed of 290 r / min and room temperature for 1.5 min, cement is added, and mixing is continued at a speed of 140 r / min and room temperature for 2 min. After mixing evenly, a cementitious material is obtained;
[0121] Among them, the mass ratio of epoxy resin E51, water-based epoxy resin, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, modified nano zinc oxide, water, and cement is 65:35:14:9.5:10.5:14:2.8:16;
[0122] The cementitious material and the base aggregate are mixed at a mass ratio of 9.5:100 at a rotation speed of 140 r / min and room temperature for 1 minute, and after mixing evenly, a base slurry is obtained; the cementitious material and the surface layer aggregate are mixed at a mass ratio of 9.5:100 at a rotation speed of 140 r / min and room temperature for 1 minute, and after mixing evenly, a surface layer slurry is obtained;
[0123] The base aggregate is basalt; the surface aggregate is prepared by mixing machine-made sand and pretreated polypropylene fiber in a mass ratio of 100:0.58; the pretreated polypropylene fiber is prepared by soaking the polypropylene fiber in a 1.5wt% γ-(2,3-epoxypropoxy)propyltrimethoxysilane / ethanol solution for 25 minutes and then drying it at 90°C for 2.5 hours;
[0124] The base layer slurry is poured into a mold and rammed into shape to obtain a base layer; the surface layer slurry is poured into the mold filled with the base layer, smoothed so that the surface layer slurry covers the surface of the base layer, and vibrated to form a surface layer with a thickness of 0.9 cm. It is allowed to stand and solidify for 24 hours, demolded, and cured at a humidity of 93% and a temperature of 20°C for 30 days to obtain a wear-resistant porous permeable brick material.
[0125] Example 5
[0126] This embodiment discloses a method for preparing a wear-resistant porous water-permeable brick material, comprising the following steps:
[0127] Step (1), preparing an antibacterial curing agent, a water-based epoxy resin and modified nano zinc oxide;
[0128] Wherein, the antibacterial curing agent is prepared by the following steps:
[0129] Polyethylene glycol monomethyl ether methacrylate, 1-vinyl-3-butyl imidazole bromide, acrylamide, water, and ammonium persulfate are mixed in a mass ratio of 30:30:60:120:0.6, reacted at 60° C. for 10 hours, and dried at 60° C. for 48 hours after the reaction to obtain an antibacterial curing agent;
[0130] The waterborne epoxy resin is prepared by the following steps:
[0131] S11, epoxy resin E51, protocatechuic acid, and p-toluenesulfonic acid monohydrate were mixed in a mass ratio of 420:30:4.2, and reacted at 120°C for 5 hours in a nitrogen atmosphere. After the reaction was completed, a crude reaction product was obtained, and water 5 times the mass of the crude reaction product was added for extraction, and the liquids were separated. The organic phase was taken and dried at 60°C for 8 hours to obtain a protocatechuic acid-based epoxy resin;
[0132] S12, mixing protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, and ethanol, adding 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt, reacting at 65° C. for 2 h, and after the reaction, removing most of the solvent by rotary evaporation at 60° C. to obtain a water-based epoxy resin;
[0133] Among them, the mass ratio of protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, ethanol, and 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt is 420:90:40:65;
[0134] The modified nano zinc oxide is prepared by the following steps:
[0135] S21, adding 1 mol / L acetic acid aqueous solution to 95wol% ethanol aqueous solution to adjust the pH value to 5, adding 3-aminopropyltriethoxysilane dropwise for 10 min, and after the addition is completed, hydrolyzing at a speed of 400 r / min and room temperature for 7 min, adding nano zinc oxide dispersion after hydrolysis, and reacting at room temperature for 4 h. After the reaction is completed, centrifuging, filtering, taking the filter cake, adding ethanol 8 times the mass of the filter cake to wash three times, and drying at 80°C for 12 h to obtain amino nano zinc oxide;
[0136] The mass ratio of 95wol% ethanol aqueous solution, nano zinc oxide dispersion and 3-aminopropyltriethoxysilane is 150:11:5; the nano zinc oxide dispersion is prepared by mixing nano zinc oxide and ethanol in a mass ratio of 1:10 and then ultrasonically dispersing for 20 minutes;
[0137] S22, L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride was mixed with N,N-dimethylformamide, and an amino nano zinc oxide dispersion was added, and the mixture was stirred at 5°C for 88 hours. After the reaction was completed, a crude reaction product was obtained, and ether with a mass of 10 times that of the crude reaction product was added, and the mixture was filtered. The filter cake was taken, and N,N-dimethylformamide and ether with a mass of 10 times that of the filter cake were added in turn for washing, and the mixture was dried at 60°C for 24 hours to obtain an intermediate product;
[0138] The mass ratio of L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride, N,N-dimethylformamide, and amino nano zinc oxide dispersion is 5:100:100; the amino nano zinc oxide dispersion is prepared by mixing amino nano zinc oxide and N,N-dimethylformamide at a mass ratio of 1:100 and then ultrasonically dispersing for 20 minutes;
[0139] The intermediate product was mixed with 33wt% hydrogen bromide acetic acid solution at a mass ratio of 1:30, and reacted under reflux conditions for 3h. After the reaction was completed, the mixture was centrifuged, and the centrifugal precipitate was taken, and methanol 8 times the mass of the centrifugal precipitate was added to wash three times, and dried at 60°C for 18h to obtain modified nano zinc oxide;
[0140] Step (2), mixing epoxy resin E51, water-based epoxy resin, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, modified nano zinc oxide, and water at a speed of 295 r / min and room temperature for 1.5 min, adding cement, and continuing to mix at a speed of 145 r / min and room temperature for 2 min. After mixing evenly, a cementitious material is obtained;
[0141] Among them, the mass ratio of epoxy resin E51, water-based epoxy resin, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, modified nano zinc oxide, water, and cement is 60:40:15:10:10:15:3:18;
[0142] The cementitious material and the base aggregate are mixed at a mass ratio of 10:100 at a rotation speed of 145 r / min and room temperature for 1 minute, and after mixing evenly, a base slurry is obtained; the cementitious material and the surface layer aggregate are mixed at a mass ratio of 10:100 at a rotation speed of 145 r / min and room temperature for 1 minute, and after mixing evenly, a surface layer slurry is obtained;
[0143] The base aggregate is basalt; the surface aggregate is prepared by mixing machine-made sand and pretreated polypropylene fiber in a mass ratio of 100:0.6; the pretreated polypropylene fiber is prepared by soaking the polypropylene fiber in a 1.5wt% γ-(2,3-epoxypropoxy)propyltrimethoxysilane / ethanol solution for 20 minutes and then drying it at 100°C for 2 hours;
[0144] The base layer slurry is poured into a mold and rammed into shape to obtain a base layer; the surface layer slurry is poured into the mold filled with the base layer, smoothed so that the surface layer slurry covers the surface of the base layer, and vibrated to form a surface layer with a thickness of 1 cm. It is allowed to stand and solidify for 26 hours, demolded, and cured at a humidity of 95% and a temperature of 22°C for 28 days to obtain a wear-resistant porous permeable brick material.
[0145] Comparative Example 1
[0146] This comparative example discloses a method for preparing a water-permeable brick material, comprising the following steps:
[0147] Step (1), preparing an antibacterial curing agent, a water-based epoxy resin and modified nano zinc oxide;
[0148] Wherein, the antibacterial curing agent is prepared by the following steps:
[0149] Polyethylene glycol monomethyl ether methacrylate, 1-vinyl-3-butyl imidazole bromide, acrylamide, water, and ammonium persulfate are mixed in a mass ratio of 25:25:50:100:0.4, reacted at 50° C. for 12 hours, and dried at 50° C. for 56 hours after the reaction to obtain an antibacterial curing agent;
[0150] The waterborne epoxy resin is prepared by the following steps:
[0151] S11, epoxy resin E51, protocatechuic acid, and p-toluenesulfonic acid monohydrate were mixed in a mass ratio of 390:20:3.9, and reacted in a nitrogen atmosphere at 100°C for 6 hours. After the reaction was completed, a crude reaction product was obtained, and water 4 times the mass of the crude reaction product was added for extraction, and the liquids were separated. The organic phase was taken and dried at 50°C for 12 hours to obtain a protocatechuic acid-based epoxy resin;
[0152] S12, mixing protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, and ethanol, adding 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt, reacting at 55° C. for 3 h, and after the reaction, removing most of the solvent by rotary evaporation at 50° C. to obtain a water-based epoxy resin;
[0153] Wherein, the mass ratio of protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, ethanol, and 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt is 400:60:30:55;
[0154] Step (2), epoxy resin E51, water-based epoxy resin, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, and water are mixed at a speed of 275 r / min and room temperature for 2 minutes, cement is added, and mixing is continued at a speed of 135 r / min and room temperature for 3 minutes. After mixing evenly, a cementitious material is obtained;
[0155] Among them, the mass ratio of epoxy resin E51, water-based epoxy resin, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, water, and cement is 90:20:10:8:12:2.2:12;
[0156] The cementitious material and the base aggregate are mixed at a mass ratio of 8:100 at a rotation speed of 135 r / min and room temperature for 2 minutes, and after mixing evenly, a base slurry is obtained; the cementitious material and the surface layer aggregate are mixed at a mass ratio of 8:100 at a rotation speed of 135 r / min and room temperature for 2 minutes, and after mixing evenly, a surface layer slurry is obtained;
[0157] The base aggregate is basalt; the surface aggregate is prepared by mixing machine-made sand and pretreated polypropylene fiber in a mass ratio of 100:0.5; the pretreated polypropylene fiber is prepared by soaking the polypropylene fiber in a 1wt% γ-(2,3-epoxypropoxy)propyltrimethoxysilane / ethanol solution for 30 minutes and then drying it at 80°C for 3 hours;
[0158] The base layer slurry is poured into a mold and rammed into shape to obtain a base layer; the surface layer slurry is poured into the mold filled with the base layer, smoothed so that the surface layer slurry covers the surface of the base layer, and vibrated to form a surface layer with a thickness of 0.5 cm. It is allowed to stand and solidify for 20 hours, demolded, and cured at a humidity of 90% and a temperature of 18°C for 30 days to obtain a permeable brick material.
[0159] Comparative Example 2
[0160] This comparative example discloses a method for preparing a water-permeable brick material, comprising the following steps:
[0161] Step (1), preparing an antibacterial curing agent and modified nano zinc oxide;
[0162] Wherein, the antibacterial curing agent is prepared by the following steps:
[0163] Polyethylene glycol monomethyl ether methacrylate, 1-vinyl-3-butyl imidazole bromide, acrylamide, water, and ammonium persulfate are mixed in a mass ratio of 25:25:50:100:0.4, reacted at 50° C. for 12 hours, and dried at 50° C. for 56 hours after the reaction to obtain an antibacterial curing agent;
[0164] The modified nano zinc oxide is prepared by the following steps:
[0165] S11, add 1 mol / L acetic acid aqueous solution to 95wol% ethanol aqueous solution to adjust the pH value to 4.5, add 3-aminopropyltriethoxysilane dropwise for 8 min, after the addition is completed, hydrolyze at a speed of 300 r / min and room temperature for 5 min, add nano zinc oxide dispersion after hydrolysis, react at room temperature for 2 h, after the reaction is completed, centrifuge, filter, take the filter cake, add ethanol 5 times the mass of the filter cake to wash three times, and dry at 70°C for 16 h to obtain amino nano zinc oxide;
[0166] The mass ratio of 95wol% ethanol aqueous solution, nano zinc oxide dispersion and 3-aminopropyltriethoxysilane is 140:9:4.5; the nano zinc oxide dispersion is prepared by mixing nano zinc oxide and ethanol in a mass ratio of 1:8 and then ultrasonically dispersing for 10 minutes;
[0167] S12, L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride was mixed with N,N-dimethylformamide, and an amino nano zinc oxide dispersion was added, and the mixture was stirred at 0°C for 96 hours. After the reaction was completed, a crude reaction product was obtained, and ether with a mass of 8 times that of the crude reaction product was added, and the mixture was filtered. The filter cake was taken, and N,N-dimethylformamide and ether with a mass of 8 times that of the filter cake were added in turn for washing, and the mixture was dried at 50°C for 30 hours to obtain an intermediate product;
[0168] The mass ratio of L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride, N,N-dimethylformamide, and amino nano zinc oxide dispersion is 5:90:90; the amino nano zinc oxide dispersion is prepared by mixing amino nano zinc oxide and N,N-dimethylformamide at a mass ratio of 1:90 and then ultrasonically dispersing for 10 minutes;
[0169] The intermediate product was mixed with 33wt% of hydrogen bromide acetic acid solution at a mass ratio of 1:25, and reacted under reflux conditions for 2h. After the reaction was completed, the mixture was centrifuged, and the centrifugal precipitate was taken, and methanol 6 times the mass of the centrifugal precipitate was added to wash three times, and dried at 50°C for 24h to obtain modified nano zinc oxide;
[0170] Step (2), epoxy resin E51, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, modified nano zinc oxide, and water are mixed at a speed of 275 r / min and room temperature for 2 minutes, cement is added, and mixing is continued at a speed of 135 r / min and room temperature for 3 minutes. After mixing evenly, a cementitious material is obtained;
[0171] Among them, the mass ratio of epoxy resin E51, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, modified nano zinc oxide, water, and cement is 100:10:8:12:10:2.2:12;
[0172] The cementitious material and the base aggregate are mixed at a mass ratio of 8:100 at a rotation speed of 135 r / min and room temperature for 2 minutes, and after mixing evenly, a base slurry is obtained; the cementitious material and the surface layer aggregate are mixed at a mass ratio of 8:100 at a rotation speed of 135 r / min and room temperature for 2 minutes, and after mixing evenly, a surface layer slurry is obtained;
[0173] The base aggregate is basalt; the surface aggregate is prepared by mixing machine-made sand and pretreated polypropylene fiber in a mass ratio of 100:0.5; the pretreated polypropylene fiber is prepared by soaking the polypropylene fiber in a 1wt% γ-(2,3-epoxypropoxy)propyltrimethoxysilane / ethanol solution for 30 minutes and then drying it at 80°C for 3 hours;
[0174] The base layer slurry is poured into a mold and rammed into shape to obtain a base layer; the surface layer slurry is poured into the mold filled with the base layer, smoothed so that the surface layer slurry covers the surface of the base layer, and vibrated to form a surface layer with a thickness of 0.5 cm. It is allowed to stand and solidify for 20 hours, demolded, and cured at a humidity of 90% and a temperature of 18°C for 30 days to obtain a permeable brick material.
[0175] Comparative Example 3
[0176] This comparative example discloses a method for preparing a water-permeable brick material, comprising the following steps:
[0177] Step (1), preparing an antibacterial curing agent, a water-based epoxy resin and modified nano zinc oxide;
[0178] Wherein, the antibacterial curing agent is prepared by the following steps:
[0179] Polyethylene glycol monomethyl ether methacrylate, 1-vinyl-3-butyl imidazole bromide, acrylamide, water, and ammonium persulfate are mixed in a mass ratio of 25:25:50:100:0.4, reacted at 50° C. for 12 hours, and dried at 50° C. for 56 hours after the reaction to obtain an antibacterial curing agent;
[0180] The waterborne epoxy resin is prepared by the following steps:
[0181] S11, epoxy resin E51, protocatechuic acid, and p-toluenesulfonic acid monohydrate were mixed in a mass ratio of 390:20:3.9, and reacted in a nitrogen atmosphere at 100°C for 6 hours. After the reaction was completed, a crude reaction product was obtained, and water 4 times the mass of the crude reaction product was added for extraction, and the liquids were separated. The organic phase was taken and dried at 50°C for 12 hours to obtain a protocatechuic acid-based epoxy resin;
[0182] S12, mixing protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, and ethanol, adding 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt, reacting at 55° C. for 3 h, and after the reaction, removing most of the solvent by rotary evaporation at 50° C. to obtain a water-based epoxy resin;
[0183] Wherein, the mass ratio of protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, ethanol, and 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt is 400:60:30:55;
[0184] The modified nano zinc oxide is prepared by the following steps:
[0185] S21, add 1 mol / L acetic acid aqueous solution to 95wol% ethanol aqueous solution to adjust the pH value to 4.5, add 3-aminopropyltriethoxysilane dropwise for 8 min, after the addition is completed, hydrolyze at a speed of 300 r / min and room temperature for 5 min, add nano zinc oxide dispersion after hydrolysis, react at room temperature for 2 h, after the reaction is completed, centrifuge, filter, take the filter cake, add 5 times the mass of ethanol to wash three times, dry at 70°C for 16 h, and obtain amino nano zinc oxide;
[0186] The mass ratio of 95wol% ethanol aqueous solution, nano zinc oxide dispersion and 3-aminopropyltriethoxysilane is 140:9:4.5; the nano zinc oxide dispersion is prepared by mixing nano zinc oxide and ethanol in a mass ratio of 1:8 and then ultrasonically dispersing for 10 minutes;
[0187] S22, L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride was mixed with N,N-dimethylformamide, and an amino nano zinc oxide dispersion was added, and the mixture was stirred at 0°C for 96 hours. After the reaction was completed, a crude reaction product was obtained, and ether with a mass of 8 times that of the crude reaction product was added, and the mixture was filtered. The filter cake was taken, and N,N-dimethylformamide and ether with a mass of 8 times that of the filter cake were added in turn for washing, and the mixture was dried at 50°C for 30 hours to obtain an intermediate product;
[0188] The mass ratio of L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride, N,N-dimethylformamide, and amino nano zinc oxide dispersion is 5:90:90; the amino nano zinc oxide dispersion is prepared by mixing amino nano zinc oxide and N,N-dimethylformamide at a mass ratio of 1:90 and then ultrasonically dispersing for 10 minutes;
[0189] The intermediate product was mixed with 33wt% of hydrogen bromide acetic acid solution at a mass ratio of 1:25, and reacted under reflux conditions for 2h. After the reaction was completed, the mixture was centrifuged, and the centrifugal precipitate was taken, and methanol 6 times the mass of the centrifugal precipitate was added to wash three times, and dried at 50°C for 24h to obtain modified nano zinc oxide;
[0190] Step (2), epoxy resin E51, water-based epoxy resin, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, modified nano zinc oxide, and water are mixed at a speed of 275 r / min and room temperature for 2 minutes, cement is added, and mixing is continued at a speed of 135 r / min and room temperature for 3 minutes. After mixing evenly, a cementitious material is obtained;
[0191] Among them, the mass ratio of epoxy resin E51, water-based epoxy resin, active diluent polyethylene glycol diglycidyl ether, antibacterial curing agent, curing agent tetraethylene pentamine, modified nano zinc oxide, water, and cement is 80:20:10:8:12:10:2.2:12;
[0192] The cementitious material and the base aggregate are mixed at a mass ratio of 8:100 at a rotation speed of 135 r / min and room temperature for 2 minutes, and after mixing evenly, a base slurry is obtained; the cementitious material and the surface layer aggregate are mixed at a mass ratio of 8:100 at a rotation speed of 135 r / min and room temperature for 2 minutes, and after mixing evenly, a surface layer slurry is obtained;
[0193] Among them, the base aggregate is basalt; the surface aggregate is machine-made sand;
[0194] The base layer slurry is poured into a mold and rammed into shape to obtain a base layer; the surface layer slurry is poured into the mold filled with the base layer, smoothed so that the surface layer slurry covers the surface of the base layer, and vibrated to form a surface layer with a thickness of 0.5 cm. It is allowed to stand and solidify for 20 hours, demolded, and cured at a humidity of 90% and a temperature of 18°C for 30 days to obtain a permeable brick material.
[0195] In the above embodiments and comparative examples: polyethylene glycol monomethyl ether methacrylate comes from Shanghai Aladdin Biochemical Technology Co., Ltd., Mn=480, CAS No.: 32171-39-4; 1-vinyl-3-butyl imidazole bromide comes from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No.: 1033461-45-8; epoxy resin E51 comes from Qingdao Baichen New Materials Technology Co., Ltd.; protocatechuic acid comes from Shanghai Maclean Biochemical Technology Co., Ltd., CAS No.: 99-50-3; p-toluenesulfonic acid monohydrate comes from Shanghai Maclean Biochemical Technology Co., Ltd., CAS No.: 6192-52-5; 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt comes from AlfaAesar, CAS No.: 34730-59-1; nano zinc oxide comes from Nangong Jiuxin New Materials Technology Co., Ltd., particle size 10 0nm; L-glutamic acid-5-benzyl ester-N-carboxyl ring anhydride is from Hubei Weideli Chemical Reagent Co., Ltd., CAS number: 3190-71-4; 33wt% hydrogen bromide acetic acid solution is from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., product name 33wt% hydrogen bromide acetic acid solution, CAS number: 37348-16-6; polyethylene glycol diglycidyl ether is from Shandong Jinshengtai Chemical Co., Ltd., Mw=500, epoxy value is 0.7-0.8mol / 100g; tetraethylene pentamine is from Shandong Poly Chemical Co., Ltd., CAS number: 112-57-2; cement, basalt, machine-made sand, and polypropylene fiber are all commercially available, among which cement is Tower Brand PO·42.5 cement; the particle size of basalt is 4.75-9.5mm; the particle size of machine-made sand is 2.36-4.75mm; the density of polypropylene fiber is 0.91g / cm 3 , tensile strength>400MPa, elastic modulus>3.5GPa, diameter is 18-48μm.
[0196] Test example
[0197] The performance of the permeable brick materials prepared in the examples and comparative examples was tested, and the specific results are shown in Table 1:
[0198] Table 1
[0199]
[0200] Among the various indicators in Table 1: compressive strength is measured with reference to GB / T 50081-2002 "Standard Test Method for Mechanical Properties of Ordinary Concrete"; porosity is measured with reference to ASTM C1754 "Standard Test Method for Density and Void Content of Hardened Permeable Concrete"; water retention rate is measured with reference to JG / T 376-2012 "Sand-Based Permeable Bricks"; antibacterial rate is measured with reference to JC / T897-2002 "Antibacterial Properties of Antibacterial Ceramic Products", in which the bacterial species is selected as Escherichia coli; mass loss rate is measured with reference to ASTM C1747 "Standard Test Method for Permeable Concrete by Impact and Abrasion Method".
[0201] According to the test results in Table 1, it can be seen that the permeable brick material prepared by the present invention has antibacterial and wear-resistant properties, and has a porous structure and excellent water permeability and water retention performance.
[0202] The present invention prepares modified nano zinc oxide loaded with polyglutamic acid, which has excellent water absorption and water retention properties due to the presence of free carboxyl groups in polyglutamic acid; nano zinc oxide as an inorganic antibacterial agent can improve the antibacterial properties of a substrate; using the modified nano zinc oxide loaded with polyglutamic acid as a cementitious material component can not only improve the water retention properties of the cementitious material, enhance the water permeability and water retention capacity of the permeable brick material, but also improve the antibacterial properties of the permeable brick material; in comparative example 1, no modified nano zinc oxide is added, and the nano zinc oxide lacks the effect of improving the antibacterial properties of the material, and lacks polyglutamic acid with excellent water absorption and water retention properties, so the antibacterial rate and water retention rate of comparative example 1 are lower than those of the embodiment;
[0203] The present invention prepares a protocatechuic acid-based epoxy resin having a catechol group in the side chain, and then uses the epoxy group and the amino group to react with 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt to introduce a hydrophilic sulfonate group into the main chain of the epoxy resin to make it water-based. The prepared water-based epoxy resin has good hydrophilicity. Comparative Example 2 does not add the water-based epoxy resin, and the hydrophilicity of the gelling material is reduced, so the water retention rate of Comparative Example 2 is lower than that of the embodiment.
[0204] The present invention mixes the cementitious material with the base aggregate and the surface layer aggregate respectively and then casts them to form a surface layer / base layer composite material, and obtains a permeable brick material after solidification and curing; wherein, polypropylene fiber modified by epoxy silane coupling agent is added to the surface layer aggregate to improve the wear resistance of the permeable brick material; comparative example 3 does not add pretreated polypropylene fiber, so the mass loss rate of comparative example 2 is increased, and the wear resistance is lower than that of the embodiment.
[0205] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a wear-resistant porous permeable brick material, characterized in that: The following steps are involved: Step (1), preparing waterborne epoxy resin and modified nano zinc oxide; Wherein, the waterborne epoxy resin is prepared by the following steps: Protocatechuic acid-based epoxy resin, ethylene glycol butyl ether and ethanol are mixed, 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt is added, and the reaction is carried out. After the reaction is completed, rotary evaporation is performed to obtain a water-based epoxy resin; The modified nano zinc oxide is prepared by the following steps: Mix L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride and N,N-dimethylformamide, add amino nano zinc oxide dispersion, react, add ether after the reaction, filter, wash, and dry to obtain an intermediate product; The intermediate product is mixed with a hydrogen bromide acetic acid solution, reacted, and after the reaction is completed, centrifuged, washed, and dried to obtain modified nano zinc oxide; Step (2), mixing epoxy resin E51, water-based epoxy resin, active diluent, curing agent, modified nano zinc oxide, and water, adding cement, and continuing to mix until uniformly mixed to obtain a cementitious material; wherein the curing agent is prepared by mixing an antibacterial curing agent and a curing agent; After the cementitious material and the base aggregate are evenly mixed, the base slurry is obtained; after the cementitious material and the surface aggregate are evenly mixed, the surface slurry is obtained; The base layer slurry is poured into a mold, and rammed into shape to obtain a base layer; the surface layer slurry is poured into the mold filled with the base layer, vibrated into shape, left to solidify, demoulded, and cured to obtain a wear-resistant porous permeable brick material.
2. The method for preparing a wear-resistant porous water-permeable brick material according to claim 1, characterized in that: When preparing the waterborne epoxy resin in step (1), the protocatechuic acid-based epoxy resin is prepared by the following steps: The epoxy resin E51, protocatechuic acid and p-toluenesulfonic acid monohydrate are mixed and reacted, and after the reaction is completed, extraction is performed, liquid separation is performed, and the organic phase is taken and dried to obtain a protocatechuic acid-based epoxy resin; The mass ratio of epoxy resin E51, protocatechuic acid and p-toluenesulfonic acid monohydrate is 390-420:20-30:3.9-4.2; the reaction conditions are: reacting in a nitrogen atmosphere at a temperature of 100-120° C. for 5-6 hours.
3. The method for preparing a wear-resistant porous water-permeable brick material according to claim 1, characterized in that: When preparing the water-based epoxy resin in step (1), the mass ratio of protocatechuic acid-based epoxy resin, ethylene glycol butyl ether, ethanol, and 2-[(2-aminoethyl)amino]ethanesulfonic acid sodium salt is 400-420:60-90:30-40:55-65; and the reaction conditions are: reacting at a temperature of 55-65° C. for 2-3 hours.
4. The method for preparing a wear-resistant porous water-permeable brick material according to claim 1, characterized in that: When preparing the modified nano zinc oxide in step (1), the amino nano zinc oxide is prepared by the following steps: A regulator is added to the ethanol aqueous solution to adjust the pH value, 3-aminopropyltriethoxysilane is added dropwise, and after the addition is completed, hydrolysis is performed. After the hydrolysis, a nano zinc oxide dispersion is added and reacted. After the reaction is completed, centrifugation, filtration, washing, and drying are performed to obtain amino nano zinc oxide; The conditions for dropping 3-aminopropyltriethoxysilane are: dropping for 8-10 minutes at a pH value of 4.5-5; the conditions for hydrolysis are: hydrolysis for 5-7 minutes at a rotation speed of 300-400 r / min and room temperature; the conditions for reaction are: reacting at room temperature for 2-4 hours; The mass ratio of ethanol aqueous solution, nano zinc oxide dispersion and 3-aminopropyltriethoxysilane is 140-150:9-11:4.5-5, the ethanol aqueous solution is 95wol% ethanol aqueous solution, and the nano zinc oxide dispersion is prepared by mixing nano zinc oxide and ethanol in a mass ratio of 1:8-10 and ultrasonically dispersing for 10-20 minutes.
5. The method for preparing a wear-resistant porous water-permeable brick material according to claim 1, characterized in that: In the step (1), when preparing the modified nano zinc oxide, the mass ratio of L-glutamic acid-5-benzyl ester-N-carboxyl cyclic anhydride, N,N-dimethylformamide, and amino nano zinc oxide dispersion is 5:90-100:90-100; the amino nano zinc oxide dispersion is prepared by mixing amino nano zinc oxide and N,N-dimethylformamide in a mass ratio of 1:90-100, and then ultrasonically dispersing for 10-20 minutes; when preparing the intermediate product, the reaction conditions are: stirring the reaction at a temperature of 0-5°C for 88-96 hours; The mass ratio of the intermediate product to the 33wt% hydrogen bromide acetic acid solution is 1:25-30, and the hydrogen bromide acetic acid solution is a 33wt% hydrogen bromide acetic acid solution; when preparing the modified nano zinc oxide, the reaction conditions are: reacting under reflux conditions for 2-3h.
6. The method for preparing a wear-resistant porous water-permeable brick material according to claim 1, characterized in that: In the step (2), the mass ratio of epoxy resin E51, water-based epoxy resin, active diluent, curing agent, modified nano zinc oxide, water and cement is 60-80:20-40:10-15:20:10-15:2.2-3:12-18; The active diluent is polyethylene glycol diglycidyl ether; the curing agent is prepared by mixing an antibacterial curing agent and a curing agent in a mass ratio of 8-10:10-12, and the curing agent is tetraethylenepentamine; When preparing the gelling material, the mixing conditions are: mixing at a rotation speed of 275-295 r / min and room temperature for 1.5-2 minutes; the continued mixing conditions are: mixing at a rotation speed of 135-145 r / min and room temperature for 2-3 minutes.
7. The method for preparing a wear-resistant porous water-permeable brick material according to claim 6, characterized in that: The antibacterial curing agent is prepared by the following steps: Polyethylene glycol monomethyl ether methacrylate, 1-vinyl-3-butyl imidazole bromide, acrylamide, water and ammonium persulfate are mixed and reacted, and after the reaction is completed, the mixture is dried to obtain an antibacterial curing agent; The mass ratio of polyethylene glycol monomethyl ether methacrylate, 1-vinyl-3-butyl imidazole bromide, acrylamide, water and ammonium persulfate is 25-30:25-30:50-60:100-120:0.4-0.6; and the reaction conditions are: reacting at a temperature of 50-60° C. for 10-12 hours.
8. The method for preparing a wear-resistant porous water-permeable brick material according to claim 1, characterized in that: In the step (2), the mass ratio of cementitious material to base aggregate is 8-10:100; the mass ratio of cementitious material to surface aggregate is 8-10:100; when preparing the base slurry, the mixing conditions are: mixing at a rotation speed of 135-145 r / min and room temperature for 1-2 min; when preparing the surface layer slurry, the mixing conditions are: mixing at a rotation speed of 135-145 r / min and room temperature for 1-2 min; the thickness of the surface layer is 0.5-1 cm.
9. The method for preparing a wear-resistant porous water-permeable brick material according to claim 1, characterized in that: In the step (2), the base aggregate is basalt; the surface aggregate is prepared by mixing machine-made sand and pretreated polypropylene fibers in a mass ratio of 100:0.5-0.6; the pretreated polypropylene fibers are prepared by soaking polypropylene fibers in a 1-1.5wt% γ-(2,3-epoxypropoxy)propyltrimethoxysilane / ethanol solution for 20-30 minutes and then drying them at 80-100°C for 2-3 hours.
10. A wear-resistant porous water-permeable brick material prepared by the method for preparing a wear-resistant porous water-permeable brick material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Baking-free water-permeable bricks capable of rapidly removing oil stains and preparation method for baking-free water-permeable bricks
CN106747569A